2001
DOI: 10.1121/1.1357813
|View full text |Cite
|
Sign up to set email alerts
|

Time-frequency representations of Lamb waves

Abstract: The objective of this study is to establish the effectiveness of four different time-frequency representations (TFRs)--the reassigned spectrogram, the reassigned scalogram, the smoothed Wigner-Ville distribution, and the Hilbert spectrum--by comparing their ability to resolve the dispersion relationships for Lamb waves generated and detected with optical techniques. This paper illustrates the utility of using TFRs to quantitatively resolve changes in the frequency content of these nonstationary signals, as a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
108
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(113 citation statements)
references
References 14 publications
(26 reference statements)
1
108
0
Order By: Relevance
“…Our own previous publication describes an explicit method for determining two arrival times from synthetic or experimental data based on the Wigner-Ville distribution [5]. Niethammer et al [6] provides a detailed comparison of the characteristics and relative merits of different time-frequency representations, including the Fourier spectrogram, wavelet scalogram, Wigner-Ville distribution, and Hilbert spectrum. Hurlebaus et al [7] introduced and Benz et al [8] refined an autonomous correlation-based technique for locating a notch based on time-frequency analysis of notch-scattered laser pulse-generated Lamb modes.…”
Section: Introductionmentioning
confidence: 99%
“…Our own previous publication describes an explicit method for determining two arrival times from synthetic or experimental data based on the Wigner-Ville distribution [5]. Niethammer et al [6] provides a detailed comparison of the characteristics and relative merits of different time-frequency representations, including the Fourier spectrogram, wavelet scalogram, Wigner-Ville distribution, and Hilbert spectrum. Hurlebaus et al [7] introduced and Benz et al [8] refined an autonomous correlation-based technique for locating a notch based on time-frequency analysis of notch-scattered laser pulse-generated Lamb modes.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26] It has been reported that the arrival time for group velocity at specific frequencies can be obtained by determining the magnitude of the coefficients. The theory and physical meaning of STFT derived data are discussed in the literature.…”
Section: B Experiments Data Analysismentioning
confidence: 99%
“…In fact, the features are inputs for any pattern recognition algorithm [121] While Fourier analysis only reveals the frequency content of the signal, it does not provide any information about when each of the components arrived to the sensor. In the Various techniques [122] have been used to isolate multiple closely space guided wave modes in time and frequency. Recently, wavelet transform has emerged as a very important signal processing technique for feature extraction and the selection of signals [123].…”
Section: Detection Of Structural Defects With Shm Methodsmentioning
confidence: 99%